Histopathological Studies of Chlorpyrifos Toxicity in Catfish (Global Journal of Medical Research, 2016)
Histopathological changes in different tissues induced by sub-lethal concentrations of chlorpyrifos in Heteropneustes fossilis was highly reflected in the present study. Fishes were exposed to both low (1/50 th of LC 50 ) and high concentration (1/10 th of LC 50 ) doses of chlorpyrifos for duration of 30 days. Several histopathological alternations were observed in the tissue section. Gradual degenerative changes in different organs observed were disorganization of hepatic cords, necrosis with complete loss of hepatocytes at many places, swollen gill lamellae, pyknosis of nuclear structures in many necrotic cells, vacuolation and loss of glomerular structures in kidneys and atrophy on the villi structure in the treated fish. The histopathological alterations were found to be dose dependent as the cellular alterations were more pronounced with the higher concentration of the chemicals.
Keywords: chlorpyrifos; histopathology; sub-lethal; toxicity; necrosis